Transition without metamorphosis - East Germany's regional policy reconsidered - Anja Hochberg (European Regional Science Association (ERSA), 1998)
With German unification on 3 October 1990 East Germany acquired, virtually over night, the whole institutional and legal framework of the Federal Republic. As a result, German regional policy addressed problems of structural change in the new Federal States. However, seven years on, decelerating GDP increases, an ongoing decline in employment and almost stagnant productivity gains, have put the catching-up process at risk. In addition, structural and regional divergen- ces have generally prevailed but in some cases have actually worsened. This paper argues how grave conceptual misunderstandings of developmental priorities have contributed to the unsatisfactory level of economic activity. This criticism mainly refers to the fact that the already heavily contested framework of western regional policy was transferred to East Germany without any consideration of the existing needs and developmental conditions. This paper looks first at the peculiarities of the East German economy, an economy that is characterised by an interdependent set of restrictions on supply and demand. The main features of the transfer of western regional policy will then be examined. This leads to an investigation of the appropriateness of this regional development strategy. The inescapable conclusion reached is that regional economic policy in East Germany can, for the time being, only support processes of structural change, it cannot induce sustainable growth. KEY WORDS: East Germany, Growth, Regional Development
Keywords: 330